PANDANGAN DUNIA PENGARANG DALAM NOVEL MATAHARI KARYA TERE LIYE: TINJAUAN STRUKTURALISME GENETIK - Renaldi, Vicky; Mursalim, Mursalim; Hanum, Irma Surayya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2021)
Mindset’s writer influences creation of literary works. This mindset is come from the society around writer. In literary works, mindset’s writer will become world view. This research analyzing world view of Tere Liye in Matahari novel. The theory used is Lucien Goldmann's Genetic Structuralism. World view is obtained by describing several variables, there is homology, social facts, social class and trans-individual subjects. This research describe the structure of literary works and world view. This research included in the type of library research with descriptive qualitative approach. The research data is in the form of sentences or paragraphs in the Matahari novel by Tere Liye. The data source is the Matahari novel by Tere Liye. The data collection technique focuses on reading and listening techniques. Data analysis techniques using dialectical techniques. The data presentation technique is an informal technique. The results of this research indicate that the structure of literary works consists of plot, character and setting. The plot used is a chronological plot. There are eight characters who have a influence on the storyline. The setting used is the city of Jakarta during the Orde Baru era. Homology shows that the events related to Matahari novel by Tere Liye originated from the events of the Orde Baru era. Human facts are in the form of social issues, there is discrimination, militarism, restriction of freedom and revolt movements. The social class is divided into two groups, there is the bourgeoisie represented by the Dewan Kota Zaramaraz and the proletariat represented by Raib and friends. This group is led by the character named Ali who has revolutionary ideas. Ali represents the writer in his imaginary universe. World view that the writer raises is a revolutionary world view.